Aquaculture, a Component of the Farming Systems among the Fishing Communities in Oil Producing Areas of Delta, Nigeria - Okeleke, CHUKWUJI, Christopher (Asian Journal of Agriculture and Rural Development, 2013)
The study focused on ascertaining the relative importance of aquaculture in the farming systems of Oil Producing Areas Delta State, Nigeria. A stratified random sample of 598 households from 47 communities was used. Primary data collected between the months of May 2009 and February 2011 by means of structured questionnaire, complemented by oral were analysed using both descriptive and inferential statistics. The results show that 69% of the respondents were into fishing/fish farming either as sole enterprise or in combination with other farming activities while 31% were into non-fish farming activities only. Among those involved in fishing activities, 37% were into capture fisheries, while about 32% were involved in aquaculture either as sole enterprise or in combination with other farming enterprises. The average size of fish pond was about 51 m2. The mean household net income from aquaculture per annum was about N91, 542, giving the highest returns on investment of about 45%. The study also found that households practicing aquaculture together with arable cropping generated significantly (P ≤ 0.05) highest net farm income (N127342) than the rest groups of households. The major constraints to aquaculture development were inadequate finance, high cost of feeds and water pollution problems. It was recommended that the current government efforts at boosting investment in aquaculture through microcredit should be stepped up. Local sourcing of feeds by the farmers is also encouraged.